Metadiscourse in dentistry research articles published in international and Iranian journals / Elham Basiratesfahani - Elham , Basiratesfahani (2018)
Writing is a social engaging performance in which the writer is responsible for creating an unfolding and persuasive piece of writing and also for interacting with the reader so as to secure and endorse his authorial credential. Linguistically, there exist several language features that help the writer to come up with a cohesive and reader-friendly text. Among the features are metadiscourse. Metadiscourse highlights how writers control the interactive meaning and at the same time, express their commitments and perspectives. The present study is an attempt to compare the frequency and function of metadiscourse markers in International and Iranian English dentistry articles to distinguish if the Iranian dentistry authors stick to their own native norms, which reflect their cultural identity, or follow the discourse-oriented norms and conventions when they write in English. For this purpose, 20 dentistry research articles (10 from each context) were analyzed following Hyland’s (2005a) metadiscourse model. The frequency of occurrence of each marker and its subtypes is calculated per 1000 words due to the unequal size of datasets. Then, the function of each metadiscourse marker is determined. Results indicate that Iranian writers tend to use more interactive metadiscourse markers compared to their International counterparts, while both International and Iranian writers showed a similar trend in the employment of interactional metadiscourse markers. The results of this study provide authentic material to design ESP and writing courses for dentistry writers.